2007
DOI: 10.1007/s10620-007-9880-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Proton Pump Inhibitor Use in Children: A Retrospective Review of Safety

Abstract: The objective of this work was to assess the efficacy of continuous proton pump inhibitor (PPI) therapy in children and to evaluate changes in biochemical, endoscopic, and histologic parameters during such treatment. A retrospective review of children receiving PPI therapy continuously for 1 year or more with baseline and follow-up esophageal and gastric biopsies on treatment was conducted to assess type, frequency, and duration of PPI dosing, symptom relief, gastrin levels, histologic findings, and adverse ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 45 publications
1
42
0
1
Order By: Relevance
“…No statistically significant differences in gastrin level according to omeprazole dosage, dosing frequency or treatment duration has been reported. 21 And no correlation between the degree or duration of hypergastrinemia and the Omeprazole for erosive esophagitis and gastroesophageal reflux disease in children Dovepress submit your manuscript | www.dovepress.com Dovepress presence of polyps or parietal cell changes. A mild elevation in transaminase levels has been reported.…”
Section: Omeprazole Safety and Tolerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…No statistically significant differences in gastrin level according to omeprazole dosage, dosing frequency or treatment duration has been reported. 21 And no correlation between the degree or duration of hypergastrinemia and the Omeprazole for erosive esophagitis and gastroesophageal reflux disease in children Dovepress submit your manuscript | www.dovepress.com Dovepress presence of polyps or parietal cell changes. A mild elevation in transaminase levels has been reported.…”
Section: Omeprazole Safety and Tolerabilitymentioning
confidence: 99%
“…Most common reported adverse effects have been nausea, vomiting, diarrhea, epigastric pain, skin rash, and irritability 17,[20][21][22] but generally no severe enough for patient to discontinue the drug. Only one case of anaphylactic reaction due to omeprazole has been reported, in a 14-year-old boy.…”
Section: Omeprazole Safety and Tolerabilitymentioning
confidence: 99%
“…Decreased gastric acid secretion reduces cobalamin release from dietary proteins, and longterm use may lead to cobalamin deficiency (Ruscin et al 2002). However, two studies in children observed no cobalamin deficiency among patients treated with PPI for 24-35 months (ter Heide et al 2001;Tolia and Boyer 2008) There has been an increasing use of metformin in children, mainly due to the worldwide increase of type 2 diabetes in young people (Kempf et al 2008). Metformin is also used to reduce body mass index (BMI) and insulin resistance in hyperinsulinemic obese children and adolescents (Park et al 2009).…”
Section: Pharmacological Agents Associated With Cobalamin Deficiencymentioning
confidence: 99%
“…Elevated gastrin levels have been observed in patients receiving omeprazole, but serum gastrin normalized once the drug was discontinued [39]. In addition, benign gastric changes such as parietal cell hyperplasia and gastric polyps have been observed in children and adults receiving long-term PPI therapy [81,82]. However, no carcinoid tumor formation ever has been reported in humans [81].…”
Section: Safety Profilementioning
confidence: 99%
“…Other adverse effects have been reported in elderly patients on chronic PPI therapy, such as deficiency of vitamin B 12 and increased incidence of bone fractures, but these findings have not been confirmed by recent studies [82,91]. Based on current knowledge, routine testing for vitamin B 12 deficiency is not recommended in long-term PPI users [81].…”
Section: Safety Profilementioning
confidence: 99%